Variability in the proportion of components of iodoform-based Guedes-Pinto paste mixed by dental students and pediatric dentists - Anna Carolina Volpi Mello-Moura; Juliana Fanaro; Maria Aparecida Nicoletti; Fausto Medeiros Mendes; Marcia Turolla Wanderley; Antonio Carlos Guedes-Pinto (Wolters Kluwer Medknow Publications, 2011)
Objective: Guedes-Pinto paste (GPP) is an iodoform paste used in most dental schools in Brazil. The paste is a composite of medicines (Rifocort® , camphorated paramonochlorophenol [PMCC], and iodoform) used for endodontic treatment of primary teeth. The aim of this study was to evaluate the proportion variability of GPP components when mixed by undergraduate dentistry students and pediatric dentists. Materials and Methods: The study was divided into 4 groups: G1 (15 undergraduate students), G2 (15 specialists in Pediatric Dentistry), G3 (15 professors with clinical activity), and G4 (7 professors-researchers). All volunteers prepared GPP according to the original specifications: the same visual proportion for each component. The components were weighed using an analytical balance and the percentage was calculated. Result: After normality (Kolmogorov-Smirnov) and homogeneity tests (Levene test), the data were submitted to analysis of variance and intraclass correlation coefficient tests (P<0.05). The percentage means of each respective group were as follows: Rifocort® 20.2%, 20.8%, 26.7%, 27.3%; camphorated PMCC 9.2%, 8.1%, 6.7%, 5.1%; and the iodoform 70.6%, 71.1%, 64.7%, 67.6%. There were no significant differences between groups for the component percentages. There was a high intraclass correlation coefficient (G1 0.945; G2 0.951; G3 0.921; and G4 0.870). Conclusion: The proportion of GPP was similar in all the groups, allowing us to conclude that ideal GPP proportion, based on the entire group mean, was 23.8% of Rifocort® ; 7.0% of camphorated PMCC; and 69.2% of iodoform.